Cytogenetics and molecular cytogenetics - Liehr, Thomas, 1965- (New York CRC Press, 2023)
"Genomic technologies provide the means of diagnosis and management of many human diseases. This book comprehensive summary of applications of cytogenetics and molecular cytogenetics for students, clinicians and researchers in genetics, genomics combines state-of-the-art knowledge and practical expertise from leading researchers and clinicians"--
Includes bibliographical references and index.
Keywords: Cytogenetics; Molecular genetics